2021
DOI: 10.3389/fmars.2021.664063
|View full text |Cite
|
Sign up to set email alerts
|

The Meta-Organism Response of the Environmental Generalist Pocillopora damicornis Exposed to Differential Accumulation of Heat Stress

Abstract: Coral bleaching events in the marine environment are now occurring globally, and the frequency and severity of these events are increasing. Critically, these events can cause the symbiosis between Symbiodiniaceae and their coral hosts to break down, but how the microbial community within the coral responds to bleaching is still equivocal. We investigated the impact of thermal stress exposure on the meta-organism responses of the generalist scleractinian coral species Pocillopora damicornis. Using mesocosms to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 104 publications
(145 reference statements)
2
10
2
Order By: Relevance
“…Consistently, tissue samples excluding skeletal material show lower read counts than whole fragments or mucus samples (Table 1, Meistertzheim et al, 2016;Zou et al, 2022). Specifically, for P. damicornis, read counts per sample as high as 96,134 counts have been recorded in the literature for whole fragments (Bergman et al, 2021), compared to 9,414 -12,091 for tissue samples excluding coral skeleton (Li et al, 2021;Zou et al, 2022). Pollock et al (2018) also found an average of 13,629 reads per sample in the P. damicornis mucus layer and 10,928 reads per sample in the P. damicornis skeleton, compared to only 7,317 reads per sample in the P. damicornis tissue, highlighting how sample size and read count per sample may bias the overall read count.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…Consistently, tissue samples excluding skeletal material show lower read counts than whole fragments or mucus samples (Table 1, Meistertzheim et al, 2016;Zou et al, 2022). Specifically, for P. damicornis, read counts per sample as high as 96,134 counts have been recorded in the literature for whole fragments (Bergman et al, 2021), compared to 9,414 -12,091 for tissue samples excluding coral skeleton (Li et al, 2021;Zou et al, 2022). Pollock et al (2018) also found an average of 13,629 reads per sample in the P. damicornis mucus layer and 10,928 reads per sample in the P. damicornis skeleton, compared to only 7,317 reads per sample in the P. damicornis tissue, highlighting how sample size and read count per sample may bias the overall read count.…”
Section: Discussionsupporting
confidence: 52%
“…The communities observed in Acropora and Pocillopora samples were likely also influenced by both preservation method and anthropogenic factors. While Alphaproteobacteria dominated the microbiome of both Acropora and Pocillopora in the present study, Bergman et al (2021) previously found Gammaproteobacteria to dominate the microbiome of whole Pocillopora fragments. The samples in the present study were collected directly from the reef, whereas Bergman et al (2021) collected corals and conducted an ex situ tank experiment using multiple warming trajectories, which likely influenced the differences from the microbial communities observed herein due to environmental effects.…”
Section: Comparisoncontrasting
confidence: 54%
See 2 more Smart Citations
“…OTUs present in at least 80% of the samples of the same substrate were considered members of the core microbiome, following the criterion proposed by Hernandez-Agreda et al (2016) andBergman et al (2021). As a result, the core microbiome OTUs of each substrate were present in at least 10 of 12 samples.…”
mentioning
confidence: 99%